Reseña/Review (Beilin, Katarzyna Olga, "In search of an alternative biopolitics: anti-bullfighting, animality, and the environment in contemporary Spain", Comlumbus: State University Press, 308 págs. 2015) - Prádanos, Luis (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
Reseña/Review (Beilin, Katarzyna Olga, "In search of an alternative biopolitics: anti-bullfighting, animality, and the environment in contemporary Spain", Comlumbus: State University Press, 308 págs. 2015)